Synthesis and growth mechanism of Zn0.5Cd0.5S nanohexagon dendrite. Issue 3 (24th November 2014) - Yu, Wen; Fang, Pengfei; Wang, Shaojie
Abstract : Hierarchical Zn0.5 Cd0.5 S nanohexagon dendrites were synthesized by a one-step hydrothermal method. The Zn0.5 Cd0.5 S nanohexagon dendrites were made up of nanohexagons with a side length of about 90 nm. The nanohexagons were regularly arranged forming as embranchments which were parallel to each other along certain hexagonal directions. Furthermore, these embranchments made up primary trunks shaping as dendrites. The growth mechanism of Zn0.5 Cd0.5 S nanohexagon dendrites was proposed in which molecular soft template and lowest energy principle played key roles. By adjusting the composition of the reactants, a series of Zn x Cd1– x S solid solutions could be obtained. The morphology of the synthesized Zn x Cd1– x S depended much on the x value. The UV-vis spectra absorb edges of the Zn x Cd1– x S samples continuously shifted indicating the changes of the band gap.